Is Patience Malleable via Educational Intervention? Evidence on the Role of Age in Field Experiments - Tim Kaiser; Lukas Menkhoff; Luis Oberrauch (Institute of Labor Economics (IZA), 2023)
We study the age-dependent malleability of patience via educational interventions designed to foster financial decision-making capabilities and to induce a more future-oriented mindset. We conduct a field experiment covering both youths and adults in Uganda and aggregate evidence from earlier experiments to study the generalizability of effects. In our field experiment, we find heterogenous effects by age: adults' patience and discount factors are unaffected by the intervention after 15 months follow-up, but we observe large effects on patience and estimated discount factors and field saving behavior for youth. In the meta-analysis, we find that the results are generalizable across contexts.
Keywords: C93; D15; I21; G53; 330; patience; time preferences; malleability; field experiment; educational intervention